Influence of Brand Ambassador Against Purchase Interest with Event Marketing as Intervening Variable - Yusuf, Bintang Akbar; Armiati, Reni; Sunarno, Sunarno (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of the use of brand ambassador on purchasing interest with event marketing as a intervening variable. The method used is the quantitative method (explanatory research). The population in this study were visitors event “Wave Here On 2024” who follow the Instagram accounts @mychitato and @indomilkyourway. Meanwhile, the sample of this study was 100 respondents with the technique purposive sampling. The results of this study indicate that event marketing able to mediate the influence of Seventeen as brand ambassador on purchasing interest in Indomilk and Chitato products. This explains that the ability of the variable brand ambassador (X) and event marketing (Z) in influencing the purchase interest variable (Y) by 53.8%. While the remaining 46.2% of the purchase interest variable (Y) is influenced by other variables not discussed in this study.